High-Resolution Snow Measurements combined with Active and Passive Microwave Modeling - Proksch, Martin (2015)
Snow can be regarded as one of the most complex materials on earth. Snow is a porous high temperature material which undergoes permanents change due to diagenetic and metamorphic processes. However, snow permanently influences many facets of science and society, as it is immutably bound to climatology, hydrology, natural hazards, numeric weather prediction or public transport. This thesis addresses current methodological limitations that are of critical importance when measuring snow physical properties. These limitations appear with regard to both, in- and ex-situ measurements. In-situ measurements suffer mainly from extensive measurement duration, coarse resolution or the lack of objectiveness of traditional observation techniques. Ex-situ or remote measurements follow the progress towards higher spatial resolution with active instruments, where the modeling of active microwaves has become a serious demand. Consequently, two models were developed within the thesis: first, a statistical model to efficiently derive snow physical parameters at high resolution, with particular focus on practical applicability, and second, the extension of a current microwave model to include backscattering. The first study presents a novel approach to derive snow physical parameters with high vertical resolution and in short measurement times. A statistical model was developed to derive density, specific surface area (SSA) and correlation length from the SnowMicroPen (SMP), a high resolution penetrometer. The model was calibrated using 3-D microstructural data from micro-computed tomography (CT), which lead to an accuracy in the derived parameters of 10.6, 16.4 and 23.1 %, for density, correlation length and SSA, respectively. The potential of the method was demonstrated by the retrieval of a two-dimensional stratigraphy at Kohnen Station, Antarctica, from a 46 m long SMP transect, which clearly revealed past depositional and metamorphic events. The second study systematically assessed bias, precision and spatial resolution of ...